2015
DOI: 10.1016/j.ejbas.2015.05.003
|View full text |Cite
|
Sign up to set email alerts
|

An insight into the scientific background and future perspectives for the potential uses of melatonin

Abstract: Antiepileptic Antiosteoporotic Antioxidant Cardiovascular disease Circardian rhythm Hypnotic Immunodulatory Melatonin a b s t r a c t Melatonin is one of the most versatile and ubiquitous molecule widely distributed in nature has been reported to play a role in a wide variety of physiological responses including reproduction, circadian homeostasis, sleep, retinal neuromodulation, and vasomotor responses. In most vertebrates, including humans, melatonin is synthesized primarily in the pineal gland and is regula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 160 publications
1
16
1
Order By: Relevance
“…Each of these products of rearrangement is also a potent antioxidant in its own right. Furthermore, most of these processes involve more than one ROS per step, so that one melatonin molecule has the capacity to scavenge up to 10 ROS versus the classic antioxidants that scavenge one or less ROS [17,20,70,74]. It has been found that melatonin promotes the repair of oxidized DNA.…”
Section: Antioxidantsmentioning
confidence: 99%
See 1 more Smart Citation
“…Each of these products of rearrangement is also a potent antioxidant in its own right. Furthermore, most of these processes involve more than one ROS per step, so that one melatonin molecule has the capacity to scavenge up to 10 ROS versus the classic antioxidants that scavenge one or less ROS [17,20,70,74]. It has been found that melatonin promotes the repair of oxidized DNA.…”
Section: Antioxidantsmentioning
confidence: 99%
“…Melatonin is secreted primarily by the pineal gland in response to darkness [2,13,14]. It was later found to be also present or synthesized in extrapineal sites such as retina, Harderian gland, lymphocytes, gastrointestinal tract, bone marrow cells, platelets and skin [13,[15][16][17]. The neurohormone melatonin is not stored in the pineal gland but rather is released into the bloodstream and can penetrate all body tissues [18].…”
Section: Introductionmentioning
confidence: 99%
“…Anwar et al (2015) explained that extreme temperatures caused developmental shifts and disrupting reproduction processes. Also, late planting maize may experience cooler conditions during its early vegetative growth stage and extended towards grain filling stage which may lengthens the grain filling period.…”
Section: Introductionmentioning
confidence: 99%
“…The authors outlined that in eukaryotic cells mitochondria are the main source of reactive oxygen species (ROS) and reactive nitrogen species and therefore they require specific on‐site protection. Among the endogenous antioxidant representatives, MEL and its metabolic derivatives are the most potent free radical scavengers (Zhang & Zhang, 2014) that help to struggle with free radicals, protecting live cells from oxidation processes and maintain homeostasis (Anwar et al., 2015; Galano, Tan, & Reiter, 2011; Hardeland & Poeggeler, 2003; Paredes, Korkmaz, Manchester, Tan, & Reiter, 2009; Reiter, Tan, Terron, Flores, & Czarnocki, 2007). One MEL molecule has the capacity to scavenge up to 10 ROS versus the other antioxidants that scavenge 1 or even less ROS (Tan, Manchester, Esteban‐Zubero, Zhou, & Reiter, 2015).…”
Section: Origin and Physiological Functions Of Melatoninmentioning
confidence: 99%